Effect of beta‐adrenergic blockade with carvedilol on cachexia in severe chronic heart failure: results from the COPERNICUS trial. Issue 4 (27th February 2017) - Clark, Andrew L.; Coats, Andrew J.S.; Krum, Henry; Katus, Hugo A.; Mohacsi, Paul; Salekin, Damien; Schultz, Melissa K.; Packer, Milton; Anker, Stefan D.
Abstract: Background: Cardiac cachexia frequently accompanies the progression of heart failure despite the use of effective therapies for left ventricular dysfunction. Activation of the sympathetic nervous system has been implicated in the pathogenesis of weight loss, but the effects of sympathetic antagonism on cachexia are not well defined. Methods: We prospectively evaluated changes in body weight in 2289 patients with heart failure who had dyspnoea at rest or on minimal exertion and a left ventricular ejection fraction <25%. Patients were randomly assigned (double‐blind) to receive either placebo ( n  = 1133) or carvedilol ( n  = 1156) and were followed for the occurrence of major clinical events for up to 29 months (COPERNICUS trial). Patients were not enrolled if they had signs of clinically significant fluid retention due to heart failure. Results: Patients in the carvedilol group were 33% less likely than patients in the placebo group to experience a further significant loss of weight (>6%) (95% confidence interval: 14–48%, P  = 0.002) and were 37% more likely to experience a significant gain in weight (≥5%) (95% confidence interval: 12–66%, P  = 0.002). Carvedilol's ability to prevent weight loss was most marked in patients with increased body mass index at baseline, whereas its ability to promote weight gain was most marked in patients with decreased body mass index at baseline. Increases in weight were not accompanied by evidence of fluid retention. Baseline values for body mass index and change in body weight were significant predictors of survival regardless of treatment. Conclusions: Carvedilol attenuated the development and promoted a partial reversal of cachexia in patients with severe chronic heart failure, supporting a role for prolonged sympathetic activation in the genesis of weight loss.